Characterization of Thioether‐Linked Protein Adducts of DNA Using a Raney‐Ni‐Mediated Desulfurization Method and Liquid Chromatography‐Electrospray‐Tandem Mass Spectrometry. Issue 1 (15th February 2018) - Chowdhury, Goutam; Guengerich, F. Peter
Abstract: This unit contains a complete procedure for the detection and structural characterization of DNA protein crosslinks (DPCs). The procedure also describes an approach for the quantitation of the various structurally distinct DPCs. Although various methods have been described in the literature for labile DPCs, characterization of nonlabile adducts remain a challenge. Here we present a novel approach for characterization of both labile and non‐labile adducts by the use of a combination of chemical, enzymatic, and mass spectrometric approaches. A Raney Ni‐catalyzed reductive desulfurization method was used for removal of the bulky peptide adducts, enzymatic digestion was used to digest the protein to smaller peptides and DNA to nucleosides, and finally LC‐ESI‐tandem mass spectrometry (MS) was utilized for detection and characterization of nucleoside adducts. © 2015 by John Wiley & Sons, Inc.